CRISIS ECONÓMICA DEL ECUADOR: UNA MIRADA AL SECTOR MICROEMPRESARIAL POST COVID-19: CRISIS ECONÓMICA DEL ECUADOR - Vera Ortiz, Josselyn Geovanna; Vera Barzola, Axel Xavier; Parrales Poveda, María Leonor (UNESUM - Ciencias. Revista Científica Multidisciplinaria, 2020)
This research proposes to analyze the incidence in the micro-business sector of the economic and health crisis in Ecuador from its Gross Domestic Product (GDP), unemployment and the gradual increase in poverty. Sales due to a drastic decrease in generalized demand during confinement, coupled with the lack of resources, caused the fiscal coffers to have lower income, consumption to decrease, as well as income and liquidity. A chronological documentary, bibliographic and qualitative review was carried out, which will verify the effects of the Covid-19 pandemic in this sector that moves 90% of the national economy. The results show that the figures for the economic crisis have been accentuated in the months of the state of emergency. The economy decreased by -2.4% with respect to the period of 2019. From the micro-business sector and government policies, no concrete solutions have been found to mitigate the problems of recession. However, microenterprises have become a means to boost the country's socioeconomic growth.